2012
DOI: 10.1007/s12033-012-9603-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Camellia sinensis Thaumatin-Like Protein, CsTLP in Potato Confers Enhanced Resistance to Macrophomina phaseolina and Phytophthora infestans Infection

Abstract: Thaumatin-like proteins (TLPs), a class of pathogenesis related proteins are induced in response to pathogens and exhibit antifungal property when overexpressed in transgenic plants. In the present study, we have raised transgenic potato plants overexpressing TLP gene of Camellia sinensis (CsTLP). Fungal resistance assays of transgenic potato elucidated the potential role of CsTLP in imparting tolerance to fungal pathogens, Macrophomina phaseolina (necrotrophic) and Phytophthora infestans (hemi-biotrophic). Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 66 publications
1
45
0
Order By: Relevance
“…Furthermore, the recovery of several TLP genes only in NAD at early time point and one expressed in both genotypes but strongly up-regulated in NAD confirmed the efficient response of the resistant plant against FOM1.2. TLPs are induced in response to pathogens attack and exhibit antifungal property when over-expressed in transgenic plants, probably by inhibiting hyphal growth, and spore germination (Acharya et al, 2013). The existence of calcium related-proteins in the plant nucleus, including CaM, CaM-binding protein, CDPK, and Ca 2+− CaM-regulated protein phosphatase underline the involvement of calcium in signaling (Lecourieux et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the recovery of several TLP genes only in NAD at early time point and one expressed in both genotypes but strongly up-regulated in NAD confirmed the efficient response of the resistant plant against FOM1.2. TLPs are induced in response to pathogens attack and exhibit antifungal property when over-expressed in transgenic plants, probably by inhibiting hyphal growth, and spore germination (Acharya et al, 2013). The existence of calcium related-proteins in the plant nucleus, including CaM, CaM-binding protein, CDPK, and Ca 2+− CaM-regulated protein phosphatase underline the involvement of calcium in signaling (Lecourieux et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…TLP belongs to the PR-5 family based on the amino acid sequence and structural similarities (Edens et al, 1982). Overexpression of TLP enhances tolerance to different fungus (Acharya et al, 2013; Mackintosh et al, 2007; Munis et al, 2010), salt, drought, and oxidative stresses (Munis et al, 2010). The DUF26-like protein is also involved in multiples stress tolerance, such as rice blast fungus (Kim et al, 2004), salt stress (Zhang et al, 2009), and ozone stress (Wrzaczek et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our fi nding, Zamani et al (24) have reported that transgenic canola harboring rye tlp gene could inhibit the progress of the S. sclerotiorum fungal growth (24). The same fi ndings have also reported that overexpression of tlp gene demonstrates an inhibitory eff ect on phytopathogenic fungi through inhibition of the spore germination and mycelial growth (11,25,26).…”
Section: Discussionmentioning
confidence: 57%
“…Genetic manipulation of the plants is one of the most effi cient methods for management of the fungal diseases. TLPs as a class of PR-5 family, have been isolated and characterized from diff erent plants such as corn (16), rye (23), Camellia sinensis (11) and have shown to enhance the resistance of the plans to the fungal infection or stress conditions (6)(7)16). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation